Використання 3d-друку на сучасному виробництві машинобудування - Матюшенко, В. К. (ХНУРЕ, 2020)
The given work is devoted to modern topic of 3D-printing. The use of 3D printing at the development stage or in the technological process allows you to create higher quality products cheaper and faster. The use of expensive consumables does not allow the use of three-dimensional printing for the mass production of components.
Keywords: 3D друк; автомобілебудування